2011
DOI: 10.1085/jgp.201010538
|View full text |Cite
|
Sign up to set email alerts
|

Lens intracellular hydrostatic pressure is generated by the circulation of sodium and modulated by gap junction coupling

Abstract: We recently modeled fluid flow through gap junction channels coupling the pigmented and nonpigmented layers of the ciliary body. The model suggested the channels could transport the secretion of aqueous humor, but flow would be driven by hydrostatic pressure rather than osmosis. The pressure required to drive fluid through a single layer of gap junctions might be just a few mmHg and difficult to measure. In the lens, however, there is a circulation of Na+ that may be coupled to intracellular fluid flow. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(167 citation statements)
references
References 38 publications
(70 reference statements)
8
153
2
Order By: Relevance
“…Na + transport is coupled to fluid circulation, creating a microcirculatory system that carries nutrients to the fiber cells and allows removal of metabolic waste. The intracellular passage of fluid through gap junction channels is driven by a standing hydrostatic pressure gradient within the lens (19)(20)(21). The ensemble activity of the various membrane channels and transporters that drive this microcirculatory system overcomes the lack of a lens vasculature and supports clarity, consistent with the finding that mutations in many of these channel genes have been linked to congenital cataract (22).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Na + transport is coupled to fluid circulation, creating a microcirculatory system that carries nutrients to the fiber cells and allows removal of metabolic waste. The intracellular passage of fluid through gap junction channels is driven by a standing hydrostatic pressure gradient within the lens (19)(20)(21). The ensemble activity of the various membrane channels and transporters that drive this microcirculatory system overcomes the lack of a lens vasculature and supports clarity, consistent with the finding that mutations in many of these channel genes have been linked to congenital cataract (22).…”
Section: Introductionmentioning
confidence: 56%
“…The lens depends on the coordinated activity of different channels and transporters to create a circulating current, with Na + being the primary current carrier (16,17). The transport of Na + is coupled to circulation of fluid, and the intracellular passage of fluid through gap junction channels is driven by a hydrostatic pressure gradient (19)(20)(21). If the normal lens circulation was altered in PTEN KO animals, a buildup of osmotically active solutes within the lens could increase intracellular pressure at the lens surface, leading to the observed rupture phenotype.…”
Section: Lens-specific Pten Deletion Causes Cataract and Lens Rupturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that inhibition of the Na ϩ -K ϩ -ATPase by ouabain or by replacement of extracellular Na ϩ with K ϩ significantly reduced the lens hydrostatic pressure and disrupted the lens circulation (16). WT whole lenses were incubated for 3 h in artificial aqueous humor (AAH control) and in AAH containing 1 mM ouabain or in sodium-free AAH, and GSH content was measured in cortical and nuclear fractions of lenses.…”
Section: Contribution Of the Extracellular Pathway For Maintenance Ofmentioning
confidence: 99%
“…The circulating ionic current generates fluid flow through gap junctions. Passive gap junction-mediated intracellular fluid flow is driven by hydrostatic pressure, which is highest in lens central cells and lowest in the peripheral cells (16). Solutes such as glucose are carried by extracellular water flow and are taken up into inner fiber cells by membrane glucose transporters (17).…”
mentioning
confidence: 99%